The Dialectic of the Individual and Crowd in Canetti’s Auto-da-Fe - Khan, Muhammad Usman; Janjua, Muhammad Afzal Khan (Pakistan Languages and Humanities Review, 2025)
This paper examines the dialectic of the individual and crowd in Elias Canetti’s novel, Auto-da-Fé (1935) in a bid to understand crowd’s power to commit violence against the individual self and thinking. Qualitative researches in nature, the authors have employed Theodor W. Adorno’s theorizations to analyze the violent nature of modern ‘crowd society’ pitted against the individual autonomy. Along with utilizing ‘Crowd Theory’, this study also employs Michel Foucault’s ideas regarding madness to understand the constructed nature of sane and insane in relation to power for suppressing the individual identity and freedom. This research, while discussing the tussle between crowd and individual, opines that crowd-led society is essentially paranoid. The paranoia of ‘crowd society’ creates the binaries of normal/abnormal and sane/insane leading to the loss of individual self and dignity. The study is significant and relevant in understanding the modern capitalist society and the populist movements across the world.